Insights Into Highly Improved Solar-Driven Photocatalytic Oxygen Evolution Over Integrated Ag3PO4/MoS2 Heterostructures - Cui, Xingkai; Yang, Xiaofei; Xian, Xiaozhai; Tian, Lin; Tang, Hua; Liu, Qinqin (Frontiers in Chemistry, 2018)
Oxygen evolution has been considered as the rate-determining step in photocatalytic water splitting due to its sluggish four-electron half-reaction rate, the development of oxygen-evolving photocatalysts with well-defined morphologies and superior interfacial contact is highly important for achieving high-performance solar water splitting. Herein, we report the fabrication of Ag3PO4/MoS2 nanocomposites and, for the first time, their use in photocatalytic water splitting into oxygen under LED light illumination. Ag3PO4 nanoparticles were found to be anchored evenly on the surface of MoS2 nanosheets, confirming an efficient hybridization of two semiconductor materials. A maximum oxygen-generating rate of 201.6 mol L-1 g-1 h-1 was determined when 200 mg MoS2 nanosheets were incorporated into Ag3PO4 nanoparticles, which is around 5 times higher than that of bulk Ag3PO4. Obvious enhancements in light-harvesting property, as well as electron-hole separation and charge transportation are revealed by the combination of different characterizations. ESR analysis verified that more active oxygen-containing radicals generate over illuminated Ag3PO4/MoS2 composite photocatalysts rather than irradiated Ag3PO4. The improvement in oxygen evolution performance of Ag3PO4/MoS2 composite photocatalysts is ascribed to wide spectra response in the visible-light region, more efficient charge separation and enhanced oxidation capacity in the valence band (VB). This study provides new insights into the design and development of novel composite photocatalytic materials for solar-to-fuel conversion.